Revised protocol for whole genome sequencing of Rift Valley fever (RVF) virus in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The protocol has been used for sequencing more than 15 isolates of RVF virus from human and livestock clinical samples in Kenya. The evidence link goes to a web interface where users can enter sequences with a run time of approximately one minute/genome. A manuscript has been submitted for publication.